RANCANG BANGUN MESIN PEMBUAT ES KRIM - Rosihan Wahyu Jatmiko; Sunyoto Sunyoto (JITEK (Jurnal Ilmiah Teknosains), 2021)
Ice cream is a type of food that is liked by many people, both young and old. The results of literature studies and field observations show that there are several problems such as effectiveness, efficiency, and ergonomics in the process of making ice cream. This design aims to make a machine that can function properly, effectively, efficiently, and ergonomically. The calculation of propulsion needs, power successor, v-belt speed, frame strength aims to meet the demand for ice cream targets according to the design plan. The ice cream maker uses a 0.25 HP motor with a rotation speed of 1400 rpm and a dough tube with a capacity of 16 liters. The effectiveness of the ice cream results shows that the rotation speed of 230 rpm is a good rotation speed used in the manufacturing process. Time efficiency reaches 10% because it is 2 minutes faster than the old engine. The capacity efficiency reaches 22.23% because it is able to produce 6.67 liters more. Cost efficiency reaches 55.29% or more efficient electricity costs Rp. 98.25. Ergonomic ice cream maker machine developed is very decent and better than the old machine.